KETERKAITAN KANDUNGAN TOTAL SUSPENDED SOLID (TSS) TERHADAP KELIMPAHAN BAKTERI Vibrio spp. PADA KAWASAN TAMBAK UDANG. - Istiqomah, Nurul (FAPETKAN UNTAD, 2011)
This research was done to investigate relationships between changes in total suspended solid (TSS) and total abundance of bacteria Vibrio spp., the presence of Vibrio harveyi and Vibrio parahaemolyticus in the total Vibrio spp., and the dynamics of TSS, protein and Vibrio spp. total for shrimp pond management. This study was undertaken from September 2009 to January 2010 at at the BPBPLAPU, Karawang, West Java and samples were collected from 20 points at that location. TSS analysis was done gravimetrically, while the nitrogen contents of samples was analysed with Kjehdahl and the abundance of Vibrio spp. was determined according Bacteriological Analytical Manual. The presence of Vibrio harveyi and Vibrio was determined biochemically. Data were analysed descriptively and with a regression analysis, and a dynamic model was developed. Results showed that the highest TSS density (280 mg/l) was found in area B, and the highest Vibrio spp. abundance was also located in area B (1.5 x 106 CFU/ml and 1.7 x 105 CFU/ml). The highest population for Vibrio harveyi was located in area F1 (8.6 x 105 CFU/ml), while the same parameter for Vibrio parahaemolyticus was indicated in area E1-1 (9.7 x 105 CFU/ml). The highest protein content (28%) was located in area B. Key words : Coastal aquaculture area, protein, TSS, Vibrio spp.